2008
DOI: 10.1177/0306624x08314577
|View full text |Cite
|
Sign up to set email alerts
|

Is Low Self-Control Associated With Violence Among Youths in Turkey?

Abstract: Self-control theory is tested in relation to violence on a sample of university students in Turkey. The primary findings indicate support for the theory net of the impacts of strain, deterrence, differential association, social bonding, and routine activity theories: The greater the low self-control, the greater the violence. No subdimensions of self-control have consistent significant impacts on violence. Most high-opportunity measures have positive impacts on violence. Interaction effects occur only among su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Convictions Deviance GP Off NC PC ND D LSC 46 80 32 85 32 86 Socialization 69 78 64 81 63 82 LSC and Socialization 68 79 63 82 64 numerous cross-cultural studies also support (e.g., Özbay and Köksoy 2009;Shekarkhar and Gibson 2011;Vaszonyi and Belliston 2007). However, the great difference in the relationship between low self-control and deviance in the different samples needs to be explained.…”
Section: Samplementioning
confidence: 94%
See 1 more Smart Citation
“…Convictions Deviance GP Off NC PC ND D LSC 46 80 32 85 32 86 Socialization 69 78 64 81 63 82 LSC and Socialization 68 79 63 82 64 numerous cross-cultural studies also support (e.g., Özbay and Köksoy 2009;Shekarkhar and Gibson 2011;Vaszonyi and Belliston 2007). However, the great difference in the relationship between low self-control and deviance in the different samples needs to be explained.…”
Section: Samplementioning
confidence: 94%
“…Those are manifestations of what Gottfredson and Hirschi (1990) refer to as analogous behavior, according to their theory. Some authors showed that the relationship between low selfcontrol and deviant behavior is stable across different cultural contexts (Özbay and Köksoy 2009;Shekarkhar and Gibson 2011;Vaszonyi and Belliston 2007). Cretacci (2008), on the other hand, concluded that the explanatory power of the general theory of crime is overestimated.…”
Section: The Manifestations Of Low Self-controlmentioning
confidence: 99%
“…Exceptions are a series of articles by Özbay and various colleagues that reported on tests of general strain theory (Özbay & Özcan, 2006a), social control theory (Özbay & Özcan, 2006b, 2008), and selfcontrol theory (Özbay, 2008;Özbay & Köksoy, 2009) in Turkey. Although these exceptions contributed to knowledge by testing hypotheses deduced from a variety of theories, the studies take a positivist approach and use a cross-sectional design that do not provide insight into the lived experiences of the youth over time.…”
Section: Key Findings and Implicationsmentioning
confidence: 99%
“…However, the number of the extant research on tests of theories of crime or delinquency has been very few (not to mention the absence of "local" crime theories or concepts): Merton's (1938) Gottfredson and Hirschi's (1990) selfcontrol theory (Özbay 2008b;Özbay and Köksoy 2009), neutralization techniques (Ferzan 2009), and an integration of classic strain and social control theories (Özbay 2008a). Although differential association/social learning theory has not been directly tested in Turkish context, however, the variables form this theory has been continously used as control variables in some studies (e.g., Özbay 2006b; Özbay 2015).…”
Section: Criminological Theories In Turkeymentioning
confidence: 99%
“…According to self-control theory (Gottfredson and Hirschi 1990), an indiviudal with a low self-control in the presence of opportunity is more likely to engage in criminal behavior. Self-control theory was tested in relation to violence by using sample of 974 undergraduate students at a public state university in a small city, Nigde, in 2004 in a cross-sectional study (Özbay and Köksoy 2009). The findings indicated that the lower the self control, the greater the violence.…”
Section: Self-control Theorymentioning
confidence: 99%